SISTEM INFORMASI GEOGRAFIS PERSEBARAN GURU PNS DI KABUPATEN BATANG TAHUN 2021-2023 - Muhammad Rifqi Mubarok (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Education is one of the crucial factors in constructing a developing and sustainable society. The Geographic Information System (GIS) for the Distribution of Civil Servant Teachers (PNS) in Kabupaten Batang, developed during the period of 2021-2023, aims to enhance the efficiency of teacher placement, ensure an equitable distribution, and provide a comprehensive view of the educational conditions in the region. The system focuses on interactive digital mapping, empowering users to explore and examine the distribution of PNS teachers across various districts and villages in Kabupaten Batang. Through the integration of geographic data with employment information, the system facilitates dynamic visualization of specializations, education levels, and teaching experience of teachers in each location. Users can utilize spatial analysis tools such as hotspot analysis and buffer analysis to identify areas with urgent teacher needs or plan resource redistribution. The Geographic Information System for the Distribution of PNS Teachers in Kabupaten Batang reflects a progressive step in the management of educational resources with an integrated spatial approach. It is expected that through the implementation of this system, Kabupaten Batang can optimize teacher placements, stimulate local educational development, and support long-term planning to enhance the quality of education in the region